F27. Myoclonus in demyelinating polyneuropathies: Preliminary results. (May 2018) - Gunduz, Aysegul; Tutuncu, Melih; Akalin, Mehmet A.; Uzun, Nurten; Karaali-Savrun, Feray; Kiziltan, Meral E.
Abstract : Introduction: The reports on tremor and different types of polyneuropathies have been increasing and it was suggested to be associated with cerebellar involvement in chronic inflammatory demyelinating polyneuropathy (CIDP). Apart from specific syndromes, the co-existence of polyneuropathy and myoclonus is exceptional. We previously observed cortical myoclonus in cases with inflammatory polyneuropathy who were referred for tremor analysis and aimed to analyze presence of myoclonus and its relation with clinical features in demyelinating polyneuropathies. Methods: We prospectively included all patients with inflammatory polyneuropathy who were admitted between January 2017 and June 2017 and had tremor-like, regular or irregular involuntary movements on clinical examination. All patients underwent neurological examination and multichannel surface electromyography which included upper extremity muscles as well as lower extremity and facial or neck muscles in selected cases. We also recorded long latency reflexes and somatosensory evoked potentials (SEPs) to categorize myoclonus. Results: We identified eight patients with demyelinating polyneuropathy who matched the inclusion criteria: four patients with CIDP, three patients with Guillain–Barre syndrome and one patient with Charcot-Marie-Tooth disease. The mean age was 50.5 ± 19.6 years (range: 26–81 years) and there were seven male patients. Seven out of eight patients had myoclonus, two of which were in the form of polyminimyoclonus. Others had myoclonus on both proximal and distal parts of upper extremities. Negative myoclonus was observed in four of them. Duration of myoclonus was between 30 and 100 ms. only one had duration of 200 ms. Most patients (five out of seven) had cortical myoclonus (with high-amplitude C reflex or SEPs). Conclusion: Myoclonus in the patients with polyneuropathy was irregular tremor-like, however, the electrophysiological characteristics was similar to a cortical subtype. Therefore, it would be interesting to investigate a bigger cohort of inflammatory polyneuropathies for the presence and subtypes of myoclonus and to determine associated clinical features.